Seismic and energy integrated retrofit of buildings: A critical review - Ademovic, Naida; Formisano, Antonio; Penazzato, Luca; Oliveira, Daniel V. (Frontiers in Built Environment, 2022)
The European building stock presents pertinent issues needing suitable strategies to be solved. In detail, this regards seismic safety and energy efficiency of buildings to ensure more liveable and safe cities, which represents an important goal for modern societies. Energy performance includes both comfort and saving, the latter required for a more responsible resource consumption within the building sector, having a considerable contribution to the total demand. Current strategies do not seem to be able to simultaneously solve such aspects satisfactorily, both for higher economic requirements and poor technical feasibility implied by separated and disharmonious interventions. Thus, a holistic perspective should be adopted to pursue such an ambitious objective, which has recently gained increasing attention among researchers. Current requirements are firstly highlighted to show the need for an integrated approach to building retrofit. Secondly, a critical review of integrated strategies combining seismic and energy refurbishment proposed in the literature is reported. Then, special issues are discussed, including the feasibility of an integrated approach applied to heritage buildings. This study revealed that a fully efficient strategy for integrated retrofit has not still been proposed in the literature and there are several open issues to be solved. However, current solutions may be further developed to improve them and the several options currently available demonstrated the increasing attention and importance of the topic. Finally, concluding remarks on this research topic have been drawn to promote future studies.